Kidney Disease Diagnosis in Human Using the Backward Chaining Method - Devi Ayu Ariyanto; Wiwiet Herulambang; Rani Purbaningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
Kidney disease is a disease that must be avoided by everyone. Because this disease is difficult to detect and often threatens a person's life. The problem that often occurs is that the kidneys are not functioning properly, so the body does not try to reject enough water, salt, and other materials that can cause death unless the treatment is analyzed. An accurate analytical ability is needed in determining the diagnosis of a person's kidney condition. But with the convenience of expert doctors, sometimes there are also disadvantages such as limited working hours (training) and the number of patients so they have to wait in line. The backward chaining method is an inference method that performs the search process starting from the goal, which is the conclusion of the solution to the problem at hand. Stages that must be done is to find a set of data or facts, from the facts sought conclusions that are the solution of the problem at hand. The system can be run if the user chooses a disease and chooses the symptoms that are felt and then gets a diagnosis and a solution, and medication.